Pengaruh Dosis Pupuk Dan Pembumbunan Terhadap Produksi Jagung( Zea mays L. ) - Meiyana Hikmawati (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2019)
The objectives of this research is the effect of fertilizer dosag and embedding on the yield of corn (Zea mays L). The method of the research use factorial design based on the Randomized Block Design with two factors of treatment. The first factor was fertilizer dosag (without fertilizer (P0), fertilizer dosag 250 kg/ha (P1), fertilizer dosag 500kg/ha (P2)) and second factor was embedding (one time embedding at age 3 week (B1), two time embedding at age 3 and 6 week (B2), three time embedding at age 3, 6 and 9 week (B3)) and each kombination of treatment three times replicated. The result of the research : (1) There was interaction between fertilizer dosag and embedding for parameters 100 seeds wet weight and dry weight of 100 seeds. (2) The highest yield was treatment combination P2B3 (fertilizer dosag 500kg/ha and three time embedding at age 3, 6 and 9 week) for parameters 100 seeds wet weight and dry weight of 100 seeds .(3) The highest yield treatment fertilizer dosag treatment P2 500kg/ha and embedding treatment B3 two time embedding at age 3 and 6 week.